Selection of Coconut Resistance to the Nutfall Disease (Phytophthorapalmivora Butler) The objective of this research was to select the coconut resistance to nutfall phytophthora disease. Using wounding inoculation method, detachedhits of 11 coconut populations at Pakuwon Coconut Cropping Pattern Research Station were inoculated with Phytophthora palmivora Co5 isolate. Based on the dhease lesion size at seven days after inoculation, Genjah Salak (GSK) coconutpopulation was more resistant than the - Semuel D. Runtunuwu; Meity S. Sinaga; Alex Hartana (Buletin Hama dan Penyakit Tumbuhan, 1999)
Selection of Coconut Resistance to the Nutfall Disease (Phytophthorapalmivora Butler) The objective of this research was to select the coconut resistance to nutfall phytophthora disease. Using wounding inoculation method, detachedhits of 11 coconut populations at Pakuwon Coconut Cropping Pattern Research Station were inoculated with Phytophthora palmivora Co5 isolate. Based on the dhease lesion size at seven days after inoculation, Genjah Salak (GSK) coconutpopulation was more resistant than the other coconutpopulations and showed individual resistance variation to the disease. From 238 GSK coconut trees selected, 226 (95%) trees were resistant and 12 (5%) trees were susceptible.